URGENSI PENDEKATAN EDM SEBAGAI UPAYA PENINGKATAN MUTU MADRASAH TSANAWIYAH DI PROVINSI SUMATERA SELATAN - Umar, Saipul (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
Madrasah is an educational unit that has been integrated into the national education system, so it is required to adjust the quality standards of educational outcomes, despite the fact that for more than ten years the achievement of standards is still far from expectations. Madrasah quality improvement management is a quality improvement method that is based on the school itself. So this study aims to analyze the application of quality standards as well as analyze constraints and find solutions to the quality approach in madrasas. This descriptive qualitative research uses an ethnographic study approach, which takes the object of quality administration management in secondary education units, at madrasah Tsanawiyah managed by Private Education Foundations and Islamic Boarding Schools in South Sumatra Province. The results of the study found that the constraints were mostly caused by internal factors in the madrasa, starting from the teaching and educational staff, infrastructure and supervision that were not working effectively, as well as the madrasah administrative governance system. An important finding in this study is that MTs need to take a madrasah self-evaluation (EDM) approach as a form of competency analysis and a reference for potential development starting from the internal conditions of MTs, which approach is relatively measurable and can be carried out in stages and continuously. The results of this study can be concluded that the system of governance and administrative management of MTs Suasta and MTs managed by Pondok Pesantren already needs to start improving quality starting from an overall competency analysis by changing the focus to madrasah self-evaluation.